2018
DOI: 10.1369/0022155418792032
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of FGD5 Expression in Primary Breast Cancers and Lymph Node Metastases

Abstract: Faciogenital dysplasia 5 ( FGD5) amplification drives tumor cell proliferation, and is present in 9.5% of breast cancers. We describe FGD5 expression, assess associations between FGD5 amplification and FGD5 expression, and assess FGD5 expression in relation to proliferation and prognosis. FGD5 immunohistochemistry was done on primary tumors ( n=829) and lymph node metastases ( n=231) from a cohort of Norwegian patients. We explored associations between FGD5 amplification, FGD5 expression, and proliferation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
(100 reference statements)
1
10
0
Order By: Relevance
“…The expression of FGD5-AS1 was reduced significantly in neurons subjected to OGD/R and overexpression of FGD5-AS1 could notably weaken neurons injury caused by OGD/R. FGD5 belongs to the Rho guanine nucleotide exchange factor (Rho GEF) family [8,16] and has been demonstrated to regulate proangiogenic action of VEGF in vascular endothelial cells [8]. Rho GEFs could activate Rho GTPases which modulate cytoskeleton and complicated in various cellular processes including gene expression, cell cycle progression as well as cell motility [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of FGD5-AS1 was reduced significantly in neurons subjected to OGD/R and overexpression of FGD5-AS1 could notably weaken neurons injury caused by OGD/R. FGD5 belongs to the Rho guanine nucleotide exchange factor (Rho GEF) family [8,16] and has been demonstrated to regulate proangiogenic action of VEGF in vascular endothelial cells [8]. Rho GEFs could activate Rho GTPases which modulate cytoskeleton and complicated in various cellular processes including gene expression, cell cycle progression as well as cell motility [16].…”
Section: Discussionmentioning
confidence: 99%
“…FGD5 belongs to the Rho guanine nucleotide exchange factor (Rho GEF) family [8,16] and has been demonstrated to regulate proangiogenic action of VEGF in vascular endothelial cells [8]. Rho GEFs could activate Rho GTPases which modulate cytoskeleton and complicated in various cellular processes including gene expression, cell cycle progression as well as cell motility [16]. Many Rho GEFs have been reported to be associated with the development of ischemic stroke or other cardiovascular disease, such as ARHGEF10 [9], Arhgef1 [2] etc.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 430 breast tumors found that FGD1 was amplified in 9.5% of all breast cancers surveyed, with higher cumulative risk of death from breast cancer among cases with FGD5 amplification 12 . In a separate study of 829 primary breast cancers, proportion of cancers with FGD5 expression was significantly higher with in patients with metastasis to the lymph nodes 13 . There was also some association between FGD5 amplification and nuclear localization of FGD5 13 .…”
Section: Discussionmentioning
confidence: 85%
“…In a separate study of 829 primary breast cancers, proportion of cancers with FGD5 expression was significantly higher with in patients with metastasis to the lymph nodes 13 . There was also some association between FGD5 amplification and nuclear localization of FGD5 13 . An anti-sense non-coding RNA, FGD5-AS1 is described as possessing perturbed expression in multiple cancers, including in colorectal cancer 14 and in non-small cell lung cancer (NSCLC) 15,16 .…”
Section: Discussionmentioning
confidence: 85%
“…More recent integrative analysis using 52 gene expression signatures that measure oncogenic signaling pathways identified a limited number of genes that are amplified and overexpressed in aggressive luminal subtype tumors. Among these genes, a subset (FGD5, METTL6, CPT1A, DTX3, MRPS23, EIF2S2, EIF6, and SLC2A10) was found to be essential for cell growth and, in some instances, correlated with clinical outcome [ 99 , 103 , 104 , 105 ]. This study further suggests that not only do LumA and LumB tumors express unique mutation profiles, but that these alterations result in distinct patterns of oncogenic signaling beyond differences in proliferation.…”
Section: Molecular Classification and Characterization Of Breast Cmentioning
confidence: 99%